Ethnomedicinal plants for skin and hair treatments under Meitei Traditional Medicine of Manipur, Northeast India - Khaidem, Aleena; Das, Mrinal Kumar; Ningthoujam, Sanjoy (Ecological Questions, 2025)
The Meitei community in Manipur, Northeast India, has a rich tradition of using ethnomedicinal plants for skin and hair care. As traditional ecological knowledge is declining among the community, there is a need for documentation and preservation of such knowledge. The aim of the present study is to document the plant species used by the Meitei community in Manipur for hair and skin care, as well as for treating dermatological diseases, including the preparation methods, routes of administration of herbal recipes, and the associated traditional knowledge. An ethnobotanical field study was conducted in the valley districts of Manipur, Northeast India. Plant specimens were collected, identified, and voucher specimens were collected. Ethnobotanical indices such as Use Value (UV), Informant Consensus Factor (FIC), and Fidelity Level (FL) were calculated. A total of 43 medicinal plants from 28 families were documented. Most of the recipes are prepared from leaves, fruits, and latex, while other parts are used less frequently. Routes of administration are primarily topical application. Hair care formulations are generally applied through a traditional lotion called chinghi, prepared from rice wash water. The use of traditional herbal products is closely related to the cultural traditions of the people. There is need for conservation of declining traditional ecological knowledge of the community.